2011
DOI: 10.1088/0004-637x/744/1/43
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Velocity and Density Reconstructions of the Local Universe With Cosmicflows-1

Abstract: This paper presents an analysis of the local peculiar velocity field based on the Wiener Filter reconstruction method. We used our currently available catalog of distance measurements containing 1,797 galaxies within 3000 km/s: Cosmicflows-1. The Wiener Filter method is used to recover the full 3D peculiar velocity field from the observed map of radial velocities and to recover the underlying linear density field. The velocity field within a data zone of 3000 km/s is decomposed into a local component that is g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 36 publications
(44 reference statements)
2
85
0
1
Order By: Relevance
“…The Wiener Filter method was used to recover the full 3D peculiar velocity field from the observed map of radial velocities and to recover the underlying linear density field (Courtois et al 2012). The velocity field within a data zone of 3000 km s −1 was decomposed into a local component that is generated within the data zone and a tidal one that is generated by the mass distribution outside that zone.…”
Section: Current Resultsmentioning
confidence: 99%
“…The Wiener Filter method was used to recover the full 3D peculiar velocity field from the observed map of radial velocities and to recover the underlying linear density field (Courtois et al 2012). The velocity field within a data zone of 3000 km s −1 was decomposed into a local component that is generated within the data zone and a tidal one that is generated by the mass distribution outside that zone.…”
Section: Current Resultsmentioning
confidence: 99%
“…The recipe is (1) calculate the velocity shear tensor, (2) evaluate the V-web and identify the attractors, (3) locate the bottom of a basin of attraction where the smallest eigenvalue of the shear tensor is maximal, then (4) identify the full domain of the basin of attraction by construction of the flow field in the frame of reference of the bottom of the basin of attraction. Operationally, the velocity field inferred from the Wiener Filter density reconstruction can be separated into local (divergent) and tidal components (Courtois et al 2012;Tully et al 2014). Local basins of attraction can be identified that metaphorically can be related to terrestrial watersheds.…”
Section: Discussionmentioning
confidence: 99%
“…We use the Cosmicflows-2 (CF2, Tully et al 2013) catalog of distances as a starting point for our Wiener Filter reconstruction (Courtois et al 2012(Courtois et al , 2013. The ∼ 8000 galaxy distances in CF2 are gathered according to the cosmic distance ladder and are thus from an amalgum of six methodologies: Cepheid variables, Tip of the Red Giant Branch, Surface brightness fluctuations, Tully-Fisher relation, Fundamental plane and SuperNovae Ia.…”
Section: Cosmicflows-2 and The Wiener Filter Velocity Field Reconstrumentioning
confidence: 99%